2018
DOI: 10.1186/s12913-018-3108-8
|View full text |Cite|
|
Sign up to set email alerts
|

“Availability of healthcare providers for rural veterans eligible for purchased care under the veterans choice act”

Abstract: BackgroundMilitary Veterans in the United States are more likely than the general population to live in rural areas, and often have limited geographic access to Veterans Health Administration (VHA) facilities. In an effort to improve access for Veterans living far from VHA facilities, the recently-enacted Veterans Choice Act directed VHA to purchase care from non-VHA providers for Veterans who live more than 40 miles from the nearest VHA facility. To explore potential impacts of these reforms on Veterans and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 4 publications
1
52
0
Order By: Relevance
“…Similarly, Ohl and colleagues found that VA played a greater role in providing healthcare for Veterans in counties over 40 miles from VA healthcare facilities compared with Veterans in counties within 20 miles of VA facilities. 24 Veterans' health status influenced the extent of VCP interest in that sicker individuals (i.e., higher HCC health risk scores) had higher odds of interest in VCP. This finding may be attributable to the added burden of travel or cumulative wait times experienced by Veterans needing more frequent visits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ohl and colleagues found that VA played a greater role in providing healthcare for Veterans in counties over 40 miles from VA healthcare facilities compared with Veterans in counties within 20 miles of VA facilities. 24 Veterans' health status influenced the extent of VCP interest in that sicker individuals (i.e., higher HCC health risk scores) had higher odds of interest in VCP. This finding may be attributable to the added burden of travel or cumulative wait times experienced by Veterans needing more frequent visits.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is unlikely to have impacted our results because disparities in rural areas have also been documented outside of the VA, showing lower access to non-VA specialty care. 59 In combination with very low rates of AUD medication receipt, findings from this study are concerning regarding access to evidence-based treatment for AUD among the population of PLWH living in more rural areas. While specialty addictions treatment is available in VA, it may be difficult to access care in rural areas, 56 and many patients prefer not to engage in specialty care.…”
Section: Discussionmentioning
confidence: 84%
“…We note that some patients may have accessed care outside of VA, which would not have been measured in these data. However, this is unlikely to have impacted our results because disparities in rural areas have also been documented outside of the VA, showing lower access to non‐VA specialty care …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations